The Sectoral Effects of Real Depreciations in Latin America - Lanau, Sergi (IMF Working Papers; Working Paper ;, 2017)
This papers explores the effects of real exchange rate depreciations on growth across sectors, identifying export, cost, and import-penetration channels. It tests the existence and magnitude of these channels in a panel difference-in-difference methodology. Sectors that export more to begin with, grow relatively more in response to a depreciation. The same is true of sectors where import penetration in final demand is higher. There is no evidence that depreciations reduce growth by making imported inputs more expensive. A 10 percent real depreciation would increase growth of nontraditional sectors in Latin America by 0.6-2 percentage points mostly through the export channel.